Inhibiting Factors in L2 Speaking Among Chinese EFL Primary Learners in a Private School in China: A Case Study - Maria Stephanie Rahardjo; Listyani Listyani (Kelola: Jurnal Manajemen Pendidikan, 2026)
The shift to communicative objectives in language teaching has promoted the mastery of speaking skills. Second-language (L2) speaking, in fact, is a demanding task for ESL learners because it involves integrating affective, linguistic, and social skills that may vary across cultures. In China, teachers need to delve deeper into learners’ cultural backgrounds to better motivate their L2 oral production. This case study aimed to explore how inhibiting factors affect Chinese ESL primary learners in L2 oral production. The interview took place on 11-15 November 2025. Altogether, there were 10 interviewees from a private elementary school. Two research questions to be answered in this study are: What affective, linguistic, and social factors inhibit students’ L2 speaking, and how do students experience these factors in the classroom? What kind of support from the teachers do Chinese ESL students report needing to facilitate their L2 oral production? The conclusions drawn from the study are as follows. First, participants frequently experienced low self-efficacy, demotivation, and anxiety in L2 speaking. This finding is profound because young learners are usually more adaptable in language learning compared to adults. Secondly, participants reported that difficulty in finding the right English words was the major linguistic hindrance. Therefore, they strongly needed teachers to help with vocabulary. Third, participants were reluctant to participate in a classroom presentation, mostly due to the fear of others’ judgment. The last conclusion is that participants depended on external motivation more than internal motivation to produce speech in L2. One recurring theme which underlies the findings is the fear of losing ‘face’, as the concept of ‘face’ is much valued in the Chinese culture.  This research is hoped to benefit English language teachers, both local and expatriate. Theoretically, this study will enrich Second Language Literature in the domain of learners’ differences.